Validitas dan Praktikalitas Modul Larutan Penyangga Berbasis Inkuiri Terbimbing Dilengkapi Soal-Soal Tipe HOTS - Sri Handayani; Iryani Iryani (Edukimia, 2020)
This research development aims were to create and determine validity and practicality categories of buffer solution module based on guided inquiry equipped with HOTS type problems. This research was a Research and Development with Plomp development model. Instrument used was module validity and practicality questionnaire. Module was validated by 5 validators. Practicality was determined by providing a questionnaire to 2  chemistry teachers and 51 students of class XII MIPA SMAN 8 Padang. The data obtained were analysed with the Kappa Cohen formula. The result of the research obtained average kappa moment value validity (0,90), average kappa moment value practicality of teacher response (0,93) and the practicality of student response (0,84). This result showed that the module which has been developed was very valid and practical to used in learning